Synthesis and Antioxidant Activity of Selenized Apigenin - Yawen GAO; Guopeng WU; Bo HAN; Rongwu WANG; Fangming LOU (Shipin gongye ke-ji)
Selenized apigenin (Se-AP) synthesized using sodium selenite employed as a highly reactive selenide reagent and the flavonoid apigenin (AP) as a substrate was investigated in this paper. Followed by a series of analytical techniques were used to characterize structure of Se-AP and extrapolate the possible coordination structures in Se-AP. Se content of Se-AP was measured from the fluorescent spectrophotometry to be about 1.91%±0.11%. Based on the results of structural characterization analysis, there could be concluded that new Se-O and C-O-Se bonds were formed without altering the main structure of the flavonoid backbone in selenized apigenin. The Se elements were evenly distributed in Se-AP, and one possible coordination structure of Se-AP was inferred. In addition, the antioxidant activity of AP and Se-AP was investigated by designing ABTS+, DPPH, and OH radical scavenging experiments. The in vitro antioxidant results suggested that Se-AP exhibited a clearance rate of 93.82%±0.63% for ABTS+ radicals at a concentration of 400 mg/L, 39.53%±0.67% for DPPH radicals and 96.54%±0.77% for OH radicals at a concentration of 800 mg/L and the ability of scavenging DPPH free radicals was slightly enhanced, while the scavenging ability of ABTS+ and OH radicals was significantly increased (IC50 was 53.52±1.85 mg/L and 11.33±0.64 mg/L), and the scavenging ability was comparable to that of VC at 800 mg/L at the same concentration for Se-AP. Therefore, the present data indicated that selenylation modification of AP could increase the antioxidant activity and enhance the biological activity, which could offer the possibility of the development and utilization of selenized flavonoid-related foods and drugs.